PERBANDINGAN SUHU PENYIMPANAN ELEKTRODA TERHADAP KEKERASAN BAJA KARBON - Gumono Gumono; Syamsul Hadi; Bambang Irawan (INFO-TEKNIK, 2018)
The welding is the process of connecting two metals, where factors that influence are current, voltage, plate thickness, gap shape and heating temperature of the electrode. The heating of this electrode aims to stabilize the arc arising during welding. The objective of the study was to determine the maximum hardness of low carbon steel welding with E 7018, with temperature of electrode storage at temperature 50, 75 and 100 ° C. Determine the maximum change in the hardness of the welded by using heated electrodes preheated to an initial temperature of 50, 75 and 100 ° C. Compare its hardness to the standard. The specimen-making method is based on JIS Z 3121, further data are compared against the standard. The result of maximum hardness value for slit I is 175HV and for slit V 264HV in weld area with temperature 75 ° C, hardness change of 33HV for temperature 100 °C.